P-12 More than expressions of concern: measuring the impact of volunteer bereavement support. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Scott, Ros; Dundas, Sarah; Wilson, Stewart
Abstract : Introduction: The wellbeing of the bereaved people supported by Cruse Bereavement Care Scotland (CBCS) is central to all aspects of our work. It was important to find an evidence-based evaluation tool that could provide an indication of the outcomes for clients of our volunteer face-to-face counselling support. The Warwick-Edinburgh Mental Wellbeing Score (WEMWBS) was chosen and initially piloted with clients in the West of Scotland. Approach: The questionnaire consists of a positively worded 14-item scale with five response categories. CBCS volunteers use this with clients at the beginning of the initial session and again during the last session. It is quick and easy for clients to complete and volunteers can provide help to do this if required. The pilot data gave valuable information about progress made following the support given. Feedback from volunteers and clients was also overwhelmingly positive and the evaluation tool was subsequently rolled out across the organisation. Findings: Of the initial 83 clients evaluated 86% showed an improvement in wellbeing at the end of the face-to-face sessions. WEMWBS scores are grouped into three wellbeing categories Low, Moderate and High. There was significant change in the different wellbeing categories after intervention with the proportion of clients in the low wellbeing category reducing from 84% to 30%, the proportion of clients in the moderate wellbeing category increasing from 16% to 55% and the proportion of clients in the high wellbeing group from 0% to 14%. Conclusion: The introduction of WEMWBS has provided an evidence-based tool to measure the effect of our work on the mental wellbeing of clients. The overall findings suggest that CBCS volunteers have a positive impact in improving the wellbeing of the significant majority of clients. Warwick-Edinburgh Mental Well-being Scale (WEMWBS)© NHS Health Scotland, University of Warwick and University of Edinburgh, 2006, all rights reserved.